Changes in postprandial plasma malondialdehyde levels between consumption of brown rice compared to white rice in sedentary workers - Wulandari Taradita; Novi Silvia Hardiany; Wahyu Ika Wardhani (Indonesian Nutrition Association, 2026)
Background: Office workers are prone to sedentary behavior and low physical activity, which can increased oxidative stress. The effect of dietary carbohydrates on oxidative stress can be assessed through changes in Malondialdehyde (MDA) levels, typically observed 2-4 hours of postprandially. In Indonesia, white rice remains the dominant carbohydrate source, whereas brown rice is known to contain antioxidants and dietary fiber that help counteract free radicals. Objective: The study aimed to compare the effect of brown rice and white rice consumption on postprandial plasma MDA levels. Methods: A total 28 sedentary workers subjects from FKUI Salemba participated in this open label, randomized, parallel clinical trial using consecutive sampling. Subjects were allocated to consume either 150 g of white rice (IR-64/Setra Ramos variety) or 150 g of brown rice (Aek Sibundong variety). Each meal was given once accompanied by 60 g of omelette, 70 g of tofu stew, and 220 ml of water. The participants were aged 23-48 years, with 80% being female, and all had normal BMI. Results and Conclusion: Significant differences in energy intake (p=0.026) and protein intake (p=0,014) were observed between the groups. Postprandial plasma MDA levels in the brown rice group tended to decrease, though not -significantly. (p=0.0649), whereas the white rice group showed a significant increase (p=0.01). No significant difference was found between the two groups (p=0.065). Nevertheless, brown rice can still be considered a better alternative staple food than white rice, as its antioxidants and higher fiber content can protect the body's cells from diet-induced oxidative stress.